From infection to hypertension: exploring the association between urinary tract infection and development of preeclampsia - Arunaa, Roshini; Dakshinamurthy, Padmalatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preeclampsia remains a major cause of maternal and perinatal morbidity, presenting with hypertension and proteinuria after 20 weeks of gestation. Although multifactorial in origin, maternal inflammatory and endothelial dysfunction play crucial roles in its pathogenesis. Urinary tract infection (UTI), a common condition in pregnancy, has been proposed as a potential trigger for systemic inflammation contributing to preeclampsia. This study aimed to evaluate the association between UTI and the subsequent development of preeclampsia among pregnant women attending a tertiary care hospital in Chennai. Methods: A prospective cohort study was conducted from October 2023 to October 2024 at Madras Medical College, Chennai. A total of 116 pregnant women were enrolled and categorized into UTI (n=58) and non-UTI (n=58) groups based on urine routine and culture findings. Participants were followed throughout pregnancy with serial assessments of blood pressure, urine albumin, and clinical parameters each trimester. Statistical analysis was performed using Chi-square and Fisher’s exact tests, and relative risk was calculated to estimate the strength of association. Results: UTI occurred most frequently in the first trimester, whereas preeclampsia was mainly observed in the third trimester. Among women with UTI, 60% developed preeclampsia compared to 18.7% without UTI, yielding a relative risk of 3.2, signifying a significant association. Conclusions: UTI in pregnancy was associated with a 3.2-fold increased risk of preeclampsia. Early identification and prompt treatment of UTI may reduce preeclampsia-related complications. Further large-scale studies are needed to confirm this relationship.